2005
DOI: 10.1188/05.onf.682-688
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Gender Roles, Gender Power Relationships, and Sexuality in Thai Women Following Diagnosis and Treatment for Cervical Cancer

Abstract: Open discussions among women with cervical cancer, their partners, and oncology nurses are necessary to identify culturally sensitive and appropriate solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 12 publications
3
29
0
1
Order By: Relevance
“…This preliminary study is consistent with other studies, such as the study conducted by Bergmark et al (2005) revealing that 45% women who had sexual dysfunction were also abused sexually by their spouse. Similar results were also reported by the cancer survivors in studies conducted by Kritcharoen et al (2005), that is, most husbands were angry and stressed when their wife refused to have sexual intercourse.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This preliminary study is consistent with other studies, such as the study conducted by Bergmark et al (2005) revealing that 45% women who had sexual dysfunction were also abused sexually by their spouse. Similar results were also reported by the cancer survivors in studies conducted by Kritcharoen et al (2005), that is, most husbands were angry and stressed when their wife refused to have sexual intercourse.…”
Section: Discussionsupporting
confidence: 83%
“…Such findings are similar to the study results of Kritcharoen et al . (), in which the survivors believed that if they had sexual intercourse after completing treatment, it would cause cancer relapse and induce metastasis. Previous studies by Khoo (), Burke (), and Audette and Waterman () also reported the survivors' fear of pain during sexual intercourse because of vaginal shortening and drying; as well as fear of cancer relapse.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recognition by patients with MPN that their disorders may incur a significant risk of morbidity and/or mortality may result in a reprioritization of sexual activities as attention turns to survival. This trend has been observed in other malignancies and was demonstrated in an exploratory study of 400 Thai patients receiving radiotherapy for cervical cancer, in which patients were 22% less likely to believe that sexual intercourse was important to their married life after treatment …”
Section: Discussionsupporting
confidence: 59%
“…Along with the development of the concept of holism, SHC was included as a basic component of nursing care as well, while in nursing research and education remarkable advances were recorded: models for the assessment of cancer patients' sexuality were developed and, lately, promising intervention projects were implemented for the provision of intensive SHC [2,4,13,24,34,35,45,58,59,62,67,71,72,74,75,91,93,103,106,124,125]. Since then, several studies have concluded with some important findings: the majority of cancer patients report sexual issues to be a priority [79,80]; concerns about sexual function are augmented and sustained after the experience of cancer [97]; a remarkable number of individuals are willing to discuss sexual concerns with their health providers [110], while trained oncology nurses are considered to be explicitly helpful with patients' sexual problems [4,75].…”
Section: Introductionmentioning
confidence: 99%